Bell hooks and the enactment of emotion in teaching and learning across boundaries: A pedagogy of hope? - Carolissen, R; Bozalek, V; Nicholls, L; Leibowitz , B; Rohleder , P; Swartz, L (South African Journal of Higher Education, 2011)
The notion of pedagogy of hope has been conceptualised and symbolised as a significant conciliatory and propelling vision for the University of Stellenbosch. Yet few representations of hope engage with the historical and theoretical roots of this notion. These perspectives are crucial to understand in order to provide a foundation on which to build a vision for an institution such as Stellenbosch University, given its past racialised history. This article uses bell hooks’ writings on the pedagogy of hope to examine a curriculum project across the Universities of Stellenbosch and the Western Cape. Hooks, like Freire, emphasises action through dialogue but also encourages acts that disrupt privilege. Her emphasis on emotional connections with the act of teaching by her creative use of autobiography in education, is another positive contribution to the Freirian conception of a pedagogy of hope. This article uses these understandings of a pedagogy of hope by bell hooks to analyse the methodology used in an interinstitutional, interdisciplinary project entitled Community, Self and Identity (CSI). A range of participatory techniques, blended learning, critical reading, theatre, art, film, workshops and presentations were used to support students to explore their own, and their colleagues’ personal, social and professional identities. A specific focus will be placed on autobiography and what guest lecturers who were central to the project, were able to contribute in terms of bell hooks’ notions of a pedagogy of hope